MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF DAN KEMANDIRIAN BELAJAR SISWA SMA DENGAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATERI PELUANG - Silvia Ratnasari; Anton Nasrullah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
The ability to think creatively and learn independently of students is very important in learning mathematics. As a result, we require a learning model that can help students develop their creative thinking skills and independent learning, such as the Contextual Teaching and Learning (CTL) learning model. This study aims to determine whether the Contextual Teaching and Learning (CTL) model can improve students' creative thinking skills and independent learning. The method in this study is quantitative with the CTL model using the Class Action Research (CAR) method which was carried out in class XII IPS 1 SMA Pasundan 7 Bandung with 30 students. The technique used in data collection is quantitative data with a test instrument and qualitative data with a questionnaire instrument. The findings indicated that using the CTL learning model in mathematics can improve students' creative thinking skills and independence in class XII IPS 1 SMA Pasundan 7 Bandung. CTL model students outperform conventional learners in terms of creative thinking ability and mathematical learning independence. There is a link between students' mathematical learning independence and their ability to think creatively.